Miejsce nauczania historii w pijarskich profesoriach Rzeczypospolitej w XVIII wieku - Taraszkiewicz, Jacek (Biuletyn Historii Wychowania, 2011)
Stanisław Konarski, while introducing the reform of the Piarist schools, began from changing the profile of the education of the monks, who, according to the rules and constitutions of the order were supposed to be teachers. The sources concerning the handbooks used in the education of the future history professors in Rzeszów are unknown The source data regarding the preparation of monks for their teaching profession may be obtained mostly on the basis of Ordinationes Visitationis Apostolicae... approved by the authorities of the monastic order and the Pope as late as in 1754. The Ordinationes Visitationis Apostolicae...., sometimes called “school regulations”, dedicated its third part to the problems connected with the education of the Piarist orders. The reformed system of the monks’ preparation for their future work assumed two years of noviciate, followed by three years of “profesorium”, where the monks should continue their education. The seminarists, in the period of their five year long education, learned, among others, history, which they were supposed to teach later as Piarist teachers. The historical material embraced both sacred and secular history. The readings for the future teachers in the field of history were the ancient classical works, the works of Polish historiographers and also modern works from the 16th, 17th and even 18th century. In the Piarist “profesoria” the ancient, national and general modern history was taught. However, history was still supposed to support rhetoric, providing speakers with examples confirming their erudition. The regulations concerning “profesoria” emphasised the fact that the greatest benefit of history consisted in showing the youth examples of civic virtues and vices contributing to the ruin of their Motherland.